Kinome inhibition reveals a role for polo‐like kinase 1 in targeting post‐transcriptional control in cancer - Qamraa H. Al‐Qahtani; Walid N. Moghrabi; Suhad Al‐Yahya; Latifa Al‐Haj; Maher Al‐Saif; Linah Mahmoud; Falah Al‐Mohanna; Norah Al‐Souhibani; Ayodele Alaiya; Edward Hitti; Khalid S. A. Khabar (Molecular Oncology, 2021)
Dysfunctions in post‐transcriptional control are observed in cancer and chronic inflammatory diseases. Here, we employed a kinome inhibitor library (n = 378) in a reporter system selective for 3′‐untranslated region–AU‐rich elements (ARE). Fifteen inhibitors reduced the ARE‐reporter activity; among the targets is the polo‐like kinase 1 (PLK1). RNA‐seq experiments demonstrated that the PLK1 inhibitor, volasertib, reduces the expression of cytokine and cell growth ARE mRNAs. PLK1 inhibition caused accelerated mRNA decay in cancer cells and was associated with reduced phosphorylation and stability of the mRNA decay‐promoting protein, tristetraprolin (ZFP36/TTP). Ectopic expression of PLK1 increased abundance and stability of high molecular weight of ZFP36/TTP likely of the phosphorylated form. PLK1 effect was associated with the MAPK‐MK2 pathway, a major regulator of ARE‐mRNA stability, as evident from MK2 inhibition, in vitro phosphorylation, and knockout experiments. Mutational analysis demonstrates that TTP serine 186 is a target for PLK1 effect. Treatment of mice with the PLK1 inhibitor reduced both ZFP36/TTP phosphorylation in xenograft tumor tissues, and the tumor size. In cancer patients' tissues, PLK1/ARE‐regulated gene cluster was overexpressed in solid tumors and associated with poor survival. The data showed that PLK1‐mediated post‐transcriptional aberration could be a therapeutic target.